The Development of English Learning Materials for Culinary Art Program Using Four-D Model - Maula, Minhatul (RETAIN, 2021)
English is one of the compulsory subjects in high schools, both in public and vocational schools. However, the learning materials used by both are still the same. In fact, in vocational schools, English becomes English for Specific Purposes, which has unique needs based on the students’ majors, such as in the Culinary Art Program. Therefore, the development of English learning materials for this program is needed. This study used the Research and Development (R&D) method involving students majoring in Culinary Art Program at SMK Dharma Wanita Gresik. This study used the Four-D model formulated by (Thiagarajan et al., 1976) in developing learning materials. This research was conducted to investigate the implementation of the Four-D model in developing English learning materials for the Culinary Art Program and finding out the quality of Culinary Art Program English learning materials being developed in terms of its effectiveness, practicality, and readability. This study used three instruments, including a questionnaire involving one class of Culinary Art Program students, interviews involving ten students and an English teacher majoring in Culinary Art Program, and aspects (specification) of an instructional material rubric that has been validated by an English teacher of Culinary Art Program and a lecturer. The results showed that the purpose of developing English materials for the Culinary Art Program was to adjust the content and assignments based on the culinary students’ needs, where this stage is the define stage in the Four-D model. Furthermore, the needs analysis results showed that the basic competencies developed are on procedure text and offering and responding services. Moreover, the material that must be included is the theme according to the Culinary major. This stage becomes the design stage in the Four-D model. Finally, the results of the assessment of the materials that have been developed showed that they had a good quality by meeting the aspects of effectiveness, practicality, and readability. This stage referred to develop stage in the Four-D model. Keywords: Material Development, English learning materials, needs analysis, Four-D Model, basic competencies, effectiveness, practicality, readability, Culinary Art Program.